Impact of a Pharmacy-Based Glucose Management Program on Glycemic Control in an Inpatient General Medicine Population. Issue 1 (February 2014) - Efird, Leigh E.; Golden, Sherita H.; Visram, Kanizeh; Shermock, Kenneth
Abstract: Objective: A pharmacy-based glucose management program was evaluated to determine whether improved glycemic control could be achieved in an inpatient general medicine patient population.Methods: A retrospective chart review of 151 patients with blood glucose (BG) values outside the range of 70 to 180 mg/dL within a 24-hour period was conducted. Observations for the baseline group with no pharmacy program in place were collected from admissions during July 2010 and for the intervention group in October 2010. The primary goal of the study was to determine if the pharmacy program improved patient days within the BG range of 70 to 250 mg/dL. The odds of poor glycemic control for patients in the intervention versus baseline groups were assessed by multivariate generalized estimating equations. These methods were also used to assess patient characteristics associated with poor glycemic control.Results: No evidence was observed that the pharmacy program decreased the number of days spent out of the targeted blood glucose range (70–250 mg/dL; odds ratio, 1.08; 95% CI, 0.88–1.24). However, the subgroup of patients whose admission BG was < 200 mg/dL (49% of the intervention group) experienced a significant reduction in days spent out of the BG range (70–250 mg/dL; odds ratio, 0.42; 95% CI, 0.22–0.82). No improvement in glycemic control was observed in patients with an admission BG ≥ 200 mg/dL; these patients had more disease- and social-related factors associated with poor glycemic control.Conclusion: The primary finding of this analysis was that there was no global benefit of the pharmacy-based glucose management program for improving BG values compared with usual care. Patients whose admission glucose was < 200 mg/dL experienced improvement in glycemic control in the pharmacy-based program. Maintaining the BG level of the remaining patients was generally more complicated from a disease-state and social perspective and patients experienced no improvement. These patients may require a more intense, multidisciplinary approach that is better matched to the constellation of factors responsible for their condition.